Business Process Improvement Rute Distribusi Menggunakan VRP dengan Pendekatan Strategi Cluster First Route Second (Studi kasus CV Bintang Globalindo Karawang) - Sutrisno Sutrisno; Jauhari Arifin; Audi Pramudya (Fakultas Teknik, 2023)
Distribution and transportation aspects are quite crucial for the survival of a company's business and operational activities. Characteristics and conditions of the distribution aspect of a company can affect the capital and the selling price of products that consumers will accept. Then needed optimal handling of distribution, especially in the case of product distribution routes as a form of business process improvement. The purpose of this study is to carry out business process improvement in kraft paper’s distribution at CV. Bintang Globalindo. The distribution route identification process is carried out through a saving matrix with a cluster first route second strategy approach. Clustering results based on the saving matrix produce 3 route clusters with the total order for each cluster still below the maximum load capacity of 25 tons. The results of the third cluster routing with the nearest insert and nearest neighbor algorithms produce the same route, there is; 1) Karawang Cirebon–Ciamis–Karawang, 2) Karawang–Bandung–Cianjur–Sukabumi–Karawang, and 3) Karawang–Jakarta–Tangerang–Bogor–Karawang. New route has a total distance of 1.097 km or a difference of 9.41% from the initial route. In addition, the range of cargo utilities from this proposed route is 80 - 90.4%, denser than the initial route of 76.8 - 96.8%